Agri-voltaic system to enhance land productivity and income - Santra, Priyabrata; Singh, R. K.; Jain, Dilip; Yadav, O. P. (Indian Farming, 2018)
The agri-voltaic system has huge potential in farmers’ field of the country specifically in those areas where solar irradiation is available in plenty. Installation of such system will produce food as well as generate renewable-based electricity from a single land unit whereas scarce rainwater will be conserved and used efficiently. The agri-voltaic system has capacity to increase farmers’ income in a fragile ecosystem. There is scope of improving the land equivalent ratio (LER) up to 1.62 by installation of agri-voltaic system.